2006
DOI: 10.1002/bit.21298
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic examination of changes of plant cell structure in corn stover due to hot water pretreatment and enzymatic hydrolysis

Abstract: Particle size associated with accessible surface area has a significant impact on the saccharification of plant cell walls by cellulolytic enzymes. Small particle sizes of untreated cellulosic substrate are more readily hydrolyzed than large ones because of higher specific surface area. Pretreatment enlarges accessible and susceptible surface area leading to enhanced cellulose hydrolysis. These hypotheses were tested using ground corn stover in the size ranges of 425-710 and 53-75 mm. Ultrastructural changes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
82
1
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(101 citation statements)
references
References 44 publications
11
82
1
4
Order By: Relevance
“…The SAXS results suggested an increased volume of microvoids after the acid pretreatment, which could be related to the conclusion in a previous study that the presence of hollow area after acid pretreatment is due to "peeling-away" of the components in plant cell wall (Zeng et al, 2007).…”
Section: Understanding the Effects Of Sulfuric Acid Pretreatment On Bsupporting
confidence: 84%
See 1 more Smart Citation
“…The SAXS results suggested an increased volume of microvoids after the acid pretreatment, which could be related to the conclusion in a previous study that the presence of hollow area after acid pretreatment is due to "peeling-away" of the components in plant cell wall (Zeng et al, 2007).…”
Section: Understanding the Effects Of Sulfuric Acid Pretreatment On Bsupporting
confidence: 84%
“…Among these methods, diluted sulfuric acid pretreatment has been used frequently in biomass-ethanol processing (Saha et al, 2005). An important advantage of acid pretreatment is that it is able to remove most hemicellulose from biomass and increase the total surface area of cellulose for enzymatic hydrolysis (Zeng et al, 2007). The removed hemicellulose could be degraded to monosaccharides, which could be used for ethanol production or be further degraded to furfural for chemical use.…”
Section: Introductionmentioning
confidence: 99%
“…30 Sharma et al 43 conducted experiments with different particle sizes (0.088, 0.40, 1, 6 and 30 mm) of forest and agricultural residues, and found that the highest biogas yield was obtained using the smallest substrate particles (0.088 and 0.40 mm). Zheng et al 64 examined different particle sizes of corn stover and concluded that smaller particles (53-75 µm) are more susceptible to hydrolysis than larger particles (425-710 µm). Xiao et al 65 obtained higher methane yields by reducing particle sizes of alkaline pretreated corn stover from 5-20 mm to 0.075-5 mm.…”
Section: Mechanical Pretreatmentmentioning
confidence: 99%
“…Then, the samples were sprayed with AuPd (Kim and Lee 2005;Mosier et al 2005;Zeng et al 2007) and imaged with a KYKY-2800 scanning electron microscope (KYKY Technology Development Ltd., China) operated at an accelerating voltage of 10 kV.…”
Section: Scanning Electron Microscopy (Sem) Of Pretreated Poplarmentioning
confidence: 99%